PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PERPAJAKAN, SANKSI PERPAJAKAN DAN KUALITAS PELAYANANTERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR(Study di Samsat Kabupaten Tulungagung) - Rianda Lutfi; Faisol, Badrus Zaman (CV. Adiba Aisha Amira, 2023)
Taxpayer compliance isa asituation where the taxpayer is obediett and has awareness of fulfilling tax obligation. This research aims to find empirical evidence about the factors that influence taxpayer compliance. The factors tasted in this research are theinfluence of taxpayer awareness, tax knowledge,tax sanction and tax sanctions. The populations in this study weret axpayer registered at the Samsat Tulungagung office. This sample was selected using a random sampling method. The number of samples from this research was 100 taxayer registration with Samsat Tulungagung. The data analysis used is data quality testing through validity testing which includes convergent and discriminant validity, rliability testing,and inner model evaluation. Hypothesis tesing used the inner modeland outer model. The research result identified that taxpayer awerness, tax knowledge, service quality, and tax sanctions have a positive and significant effect on taxpayer compliance.